Relationship between first trimester physical activity and premature rupture of membranes: a birth cohort study in Chinese women - Chuanzhu Lv; Qian Lu; Caihong Zhang; Shijiao Yan; Huanjun Chen; Xiong-Fei Pan; Chao Fu; Rixing Wang; Xingyue Song (BMC, 2024)
Abstract Objective This study aimed to examine prospective associations of different intensity levels and types of physical activity (PA) in early pregnancy with premature rupture of membranes (PROM) among Chinese pregnant women. Methods A total of 6284 pregnant women were included from the Tongji-Shuangliu Birth Cohort. Household/caregiving, occupational, sports/exercise and transportation activities during early pregnancy were investigated by the pregnancy physical activity questionnaire (PPAQ), and the diagnosis of PROM was ascertained during the whole pregnancy. Multivariate logistic regression models were used to estimate the odds ratios (ORs) and 95% confidence interval (CI) for the associations between PA and PROM. Results Among the 6284 pregnant women, 1246 were identified to have PROM (19.8%). Women undertaking the highest level (3 third tertile) of PA during pregnancy appeared to have a lower risk of PROM [OR = 0.68, 95%CI 0.58-0.80) when compared to those at the lowest tertile of PA. Similarly, women with increased levels of light intensity activity, moderate-vigorous intensive, household/caregiving activity and meeting exercise guidelines during pregnancy were associated with reduced risks of PROM (OR = 0.69, 95% CI 0.59-0.81, OR = 0.70, 95% CI 0.60-0.82, OR = 0.62, 95% CI 0.53-0.73 and OR = 0.82, 95% CI 0.70-0.97, respectively). Conclusions High levels of PA of different intensities and PA of household/caregiving activities and meeting exercise guidelines during the first trimester were associated with a lower incidence of PROM. Trial registration The data of human participants in this study were conducted in accordance with the Helsinki Declaration. This study has been approved by the Ethics Committee of Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China ([2017] No. S225). All participants provided written informed consent prior to enrollment. A statement to confirm that all methods were carried out in accordance with relevant guidelines and regulations.